Difosfotsyn application for the treatment acute cerebral circulatory violations - Теschuk, V. I.; Теschuk, V. V. (Journal of Education, Health and Sport, 2017)
Predecessors choline contribute to the regeneration of membranes and are considered promising medication in the treatment of stroke. The most studied compounds in this class are Difosfotsyn, which is synthesized phosphatidylcholine - an important component of cell membranes. Studies indicate that by accelerating the synthesis of phospholipids, inhibition of the release of free fatty acids stabilize the membrane and reduce production of free radicals may play a role Difosfotsyn membranoprotektora. Results of clinical studies Difosfotsynu at the Military Medical Clinical Center South region with ischemic stroke and hemorrhagic stroke demonstrated high safety and potential efficacy. Application Difosfotsynu, begun in the first 24 hours of onset, safe and increases the likelihood of complete regression of neurological deficit.